Overview of World Bank CCUS Program Activities in Mexico - Mourits, Frank (Elsevier, 2018)
This paper describes Phase I of the World Bank Group's (WBG) technical assistance project for the development of carbon capture, utilization and storage (CCUS) in Mexico. Phase I was concluded in early 2016 and saw the completion of three studies: 1. A pre-feasibility study of a proposed post-combustion capture (PCC) pilot plant at a natural gas-fired combined-cycle (NGCC) power plant in Mexico. 2. A review of state-of-the-art practices related to combining carbon dioxide-enhanced oil recovery (CO2-EOR) with geological storage of CO2 in Mexico. 3. A study of the development of a CCUS regulatory framework for Mexico.